Influence of testosterone substitution on glycemic control and endothelial markers in men with newly diagnosed functional hypogonadism and type 2 diabetes mellitus: a randomized controlled trial. (2nd October 2019) - Khripun, Irina; Vorobyev, Sergey; Belousov, Igor; Kogan, Michel; Zitzmann, Michael
Abstract: Effects of testosterone (T) on the cardiovascular system of men remain controversial. The impact of T-replacement therapy (TRT) in men with functional hypogonadism and type 2 diabetes mellitus (T2DM) has to be elucidated. This study included 80 men (mean age 51.5 ± 6.3 years) with newly diagnosed T2DM (according to ADA criteria) and functional hypogonadism (according to EAU criteria). Randomization: Group1 ( n  = 40): TRT using 1%-transdermal T-gel (50 mg/day), Group2 ( n  = 40) no TRT (controls). Dietary treatment applied to both. Parameters at baseline/after 9 months: anthropometric parameters, lipids and indicators of carbohydrate metabolism (fasting glucose, insulin, HbA1c, HOMA-IR), markers of adipose tissue and EnD (leptin, resistin, p- and e-selectin, ICAM- 1, VCAM- 1 and CRP). ANCOVA for repeated measurements revealed TRT to cause a significant decrease in waist circumference (WC), HOMA-IR and HbA1c vs controls ( p  < .001, p  = .002, p  = .004, respectively). Leptin declined in subjects receiving TRT vs controls ( p  = .04). Concentrations of resistin, ICAM-1, p-selectin and CRP decreased significantly vs controls (all p  < .001); no effects for e-selectin and VCAM-1. Advanced age attenuated effects, higher delta testosterone levels augmented effects. Decrement of WC was related to decreasing markers of adipose tissue secretion/EnD. TRT in men with functional hypogonadism and T2DM improved carbohydrate metabolism and markers of endothelial dysfunction.